2006
DOI: 10.1111/j.1540-8175.2006.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Marathon Running Upon Ventricular Function as Assessed by 2D, Doppler, and Tissue‐Doppler Echocardiography

Abstract: The impact of prolonged exercise upon right ventricular (RV) function is poorly understood and to date no studies have utilized tissue-Doppler imaging (TDI). Thirty-five marathon runners (age range 18-50 years) volunteered for the study. Two-dimensional, pulsed Doppler, and TDI studies were performed one day before and immediately following race completion. Right and left ventricular (LV) longitudinal TDI myocardial velocities were acquired from the tricuspid annulus and mitral annulus, providing velocity data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
45
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 30 publications
4
45
2
Order By: Relevance
“…Although previous studies evaluated cardiac function following endurance exercise such as marathons, ironman triathlons, or MUMs (7,20,22,28,42), the present study is the first to investigate alterations in cardiac function induced by a MUM Ͼ100 h (i.e., during several days) and the first to include a measurement performed during the event. We observed that a MUM run over 4 -7 days induced 1) a specific and progressive increase of SV from pre-to postrace concomitant with an increase in diastolic filling and 2) a biphasic adaptation of HR, LV strain rates, with an initial increase from pre-to midrace and a return to baseline values from mid-to postrace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies evaluated cardiac function following endurance exercise such as marathons, ironman triathlons, or MUMs (7,20,22,28,42), the present study is the first to investigate alterations in cardiac function induced by a MUM Ͼ100 h (i.e., during several days) and the first to include a measurement performed during the event. We observed that a MUM run over 4 -7 days induced 1) a specific and progressive increase of SV from pre-to postrace concomitant with an increase in diastolic filling and 2) a biphasic adaptation of HR, LV strain rates, with an initial increase from pre-to midrace and a return to baseline values from mid-to postrace.…”
Section: Discussionmentioning
confidence: 99%
“…IT IS WELL DOCUMENTED THAT prolonged intense exercise, such as a marathon or Ironman triathlon, transitorily alters cardiac function (7,13,20,22,23,28,42). A range of 3-15 h exercising induces transient left ventricular (LV) global systolic (20, 42) and diastolic (7,23,28) dysfunctions. This phenomenon, named exercise-induced cardiac fatigue (EICF), is generally associated with the release of biochemical markers of myocardial damage (13,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodynamic changes are one of several potential factors contributing to the mechanisms of ULCs. pulmonary edema EVEN IN HEALTHY SUBJECTS EXTREMELY demanding endurance exercise leads to functional and structural cardiac and pulmonary changes, along with local and systemic responses, reflecting oxidative, metabolic, hormonal, and thermal stress, besides immunomodulation and inflammatory reaction (4,30,32,40,41,46). Whether interstitial pulmonary edema occurs in athletes performing heavy sea level exercise is debated (2,6,12,18,19,27,28,44,56).…”
mentioning
confidence: 99%
“…1 On the other hand, prolonged intense exercise, such as marathon or long distance triathlon, may cause myocardial damages as evidenced by the release of cardiac specific biochemical markers. [2][3][4][5][6] These damages are associated with a transient impairment in cardiac function characterized by global systolic 7,8 and diastolic 3,9,10 dysfunction. However, whether this dysfunction is contingent or results from an alteration in intrinsic myocardial properties is an ongoing debate.…”
mentioning
confidence: 99%